Analisis Penerapan Akuntansi Pada Usaha Coffee Shop di Kota Bogor - Roni Adi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to see the extent of the application of financial reporting by coffee shop entrepreneurs in the city of Bogor. In general, coffee shop entrepreneurs in Bogor city have conducted financial records, with the use of digital media and tools. But in accounting, almost most of them have not done financial reporting to the fullest, which is based on the reason that the business they are doing is still relatively small and also on the basis of business ownership is still under a private name. These problems often become obstacles in efforts to develop the business in a bigger direction due to external partners as capital providers or investors who cannot support due to the absence of accurate financial information data. The research used descriptive qualitative methods, data extraction was carried out by literacy studies and direct examination in the field at coffee shop businesses in Bogor City.